Volatility and Commodity Price Dynamics in Nigeria - Manasseh, Charles Osondu; Ogbuabor, Jonathan Emenike; Obinna, Obiorah K (International Journal of Economics and Financial Issues, 2016)
This study examines volatility and commodity price dynamics in Nigeria. This was estimated with the GARCH and Exponential Generalized Autoregressive Conditional Heteroschedasticity (EGARCH), while Granger Causality test was used to examine the causality direction between domestic commodity prices and spot price of commodity derivatives. The result shows that 30% of volatility in the spot international commodity market can be explained by volatility in domestic and international export commodity prices, while international oil spot prices explains 7% volatility in prices of goods consumed locally and export commodity price index explains 16% of spot price of international commodity between 2000-2013 in Nigeria. Inflation and exchange rate is shown to be significantly related to spot price volatility which accounts for its volatility also. Hence, as such, the clamor for a more stable and robust revenue generating sector cannot be over emphasized – the so much talked about diversification. Keywords: Volatility, Dynamics, Spot price, Causality, Inflation, Exchange rate JEL Classifications: E3; E32; C32; O24; F31